Development of optical nanoprobes for molecular imaging of reactive oxygen and nitrogen species - Zhen, Xu (2020)
Reactive oxygen and nitrogen species (RONS) play important roles in cell signal transduction. However, overproduction of RONS is associated with a series of pathological processes and may disrupt cellular homeostasis, causing oxidative and nitrosative stress. Accurate methods to selectively and specifically monitor RONS in living systems are required to further elucidate the biological functions of these species. Optical imaging possesses high sensitivity, high spatiotemporal resolution, and real-time imaging capability. These qualities are advantageous for the detection of RONS in living systems. This review summarizes the development of optical nanoprobes with near-infrared (NIR) fluorescent, upconversion luminescent, chemiluminescent, or photoacoustic signals for molecular imaging of RONS in living systems. In this review, we discuss the design principles and advantages of RONS-responsive activatable nanoprobes, as well as applications of these optical imaging modalities in different disease models.